(2x+7)2=9(x+2)2
(x+2)2=9(x2-4x-4)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
Dễ
Thế
Mà
Cũnhoir
Dc
Ạ
Chịu
Chắc
Phải
Ngu
Lamqs
Mới
Hỏi
Câu
Này
\(1,\\ a,=7x^3-49x^2+21x\\ b,=x^2-x-42\\ c,=x^2-16x+64\\ d,=9x^2+12x+4\\ e,=x^2-16-25+10x-x^2=10x-41\\ 2,\\ a,\Rightarrow2\left(x-7\right)=19\\ \Rightarrow x-7=\dfrac{19}{2}\Rightarrow x=\dfrac{33}{2}\\ b,\Rightarrow4x^2-20x+25-4x^2+3x-2x=50\\ \Rightarrow-19x=25\Rightarrow x=-\dfrac{25}{19}\)
Lời giải:
1.
$4x+9=0$
$4x=-9$
$x=\frac{-9}{4}$
2.
$-5x+6=0$
$-5x=-6$
$x=\frac{6}{5}$
3.
$x^2-1=0$
$x^2=1=1^2=(-1)^2$
$x=\pm 1$
4.
$x^2-9=0$
$x^2=9=3^2=(-3)^2$
$x=\pm 3$
5.
$x^2-x=0$
$x(x-1)=0$
$x=0$ hoặc $x-1=0$
$x=0$ hoặc $x=1$
6.
$x^2-2x=0$
$x(x-2)=0$
$x=0$ hoặc $x-2=0$
$x=0$ hoặc $x=2$
7.
$x^2-3x=0$
$x(x-3)=0$
$x=0$ hoặc $x-3=0$
$x=0$ hoặc $x=3$
8.
$3x^2-4x=0$
$x(3x-4)=0$
$x=0$ hoặc $3x-4=0$
$x=0$ hoặc $x=\frac{4}{3}$
e: ta có: \(4x^2+4x-6=2\)
\(\Leftrightarrow4x^2+4x-8=0\)
\(\Leftrightarrow\left(x+2\right)\left(x-1\right)=0\)
\(\Leftrightarrow\left[{}\begin{matrix}x=-2\\x=1\end{matrix}\right.\)
f: Ta có: \(2x^2+7x+3=0\)
\(\Leftrightarrow\left(x+3\right)\left(2x+1\right)=0\)
\(\Leftrightarrow\left[{}\begin{matrix}x=-3\\x=-\dfrac{1}{2}\end{matrix}\right.\)
1) Ta có: \(5\left(x-3\right)\left(x-7\right)-\left(5x+1\right)\left(x-2\right)=-8\)
\(\Leftrightarrow5\left(x^2-10x+21\right)-\left(5x^2-10x+x-2\right)=-8\)
\(\Leftrightarrow5x^2-50x+105-5x^2+9x+2+8=0\)
\(\Leftrightarrow-41x=-115\)
hay \(x=\dfrac{115}{41}\)
2) Ta có: \(x\left(x+1\right)\left(x+2\right)-\left(x+4\right)\left(3x-5\right)=84-5x\)
\(\Leftrightarrow x\left(x^2+3x+2\right)-\left(3x^2+7x-20\right)=84-5x\)
\(\Leftrightarrow x^3+3x^2+2x-3x^2-7x+20-84+5x=0\)
\(\Leftrightarrow x^3=64\)
hay x=4
3) Ta có: \(\left(9x^2-5\right)\left(x+3\right)-3x^2\left(3x+9\right)=\left(x-5\right)\left(x+4\right)-x\left(x-11\right)\)
\(\Leftrightarrow9x^3+27x^2-5x-15-9x^3-27x^2=x^2-x-20-x^2+11x\)
\(\Leftrightarrow-5x-15=10x-20\)
\(\Leftrightarrow-5x-10x=-20+15\)
\(\Leftrightarrow x=\dfrac{-5}{-15}=\dfrac{1}{3}\)
a) Ta có: \(\left(2x+7\right)^2=9\left(x+2\right)^2\)
\(\Leftrightarrow\left(2x+7\right)^2-9\left(x+2\right)^2=0\)
\(\Leftrightarrow4x^2+28x+49-9\left(x^2+4x+4\right)=0\)
\(\Leftrightarrow4x^2+28x+49-9x^2-36x-36=0\)
\(\Leftrightarrow-5x^2-8x-13=0\)
\(\Delta=\left(-8\right)^2-4\cdot\left(-5\right)\cdot\left(-13\right)=-196\)
Vì \(\Delta< 0\) nên phương trình vô nghiệm
Vậy: \(x\in\varnothing\)